Virtual Reality Technology in Physics Learning: Possibility, Trend, and Tools - Agus Setyo Budi; Dadan Sumardani; Dewi Muliyati; Fauzi Bakri; Po-Sheng Chiu; Mutoharoh Mutoharoh; Marlinda Siahaan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
This study aims to disclose how virtual reality technology has been applied to studies of learning and the possibility of virtual reality by reviewing studies that have employed the virtual reality approach. A total of 15 papers were selected from the Scopus Index database from 2015 to 2020. Content analysis showed that virtual reality and physics learning had received the most attention under the theme of student perception, especially in self-efficacy and experience, followed by satisfaction, motivation, and engagement. Trends of research development show that the use of virtual reality has proliferated recently. Moreover, HTC Vive is the most powerful device to conduct the VR study for the tool device. This study concludes that virtual reality technology provides a promising media for educational researchers.